Pemberdayaan Masyarakat dan Mahasiswa dalam Pembersihan Pantai Pulau Kabung Selatan - Aritonang, Anthoni B; Helena, Shifa; Prayitno, Dwi Imam; Idiawati, Nora; Nurdiansyah, Sy. Irwan; Risko, Risko (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
Kabung Island, which is located in the Bengkayang Regency Government area, is one of 226 small islands in West Kalimantan. Busy visits to the island during the school holidays and weekends have resulted in a large distribution of garbage in the waters and coasts of the island, and if it is not addressed promptly, it can cause global water problems. The Lecturer Team of the Department of Marine Affairs at the University of Tanjungpura as the implementation team of PKM activities to clean the beaches of Kabung Island, together with all the islanders and students of the Department of Marine Affairs, dive in cleaning the beaches and waters close to residential areas, sorting and collecting garbage, then burning and stockpiling it so that it does not get worse. accumulate and more and more enter the water bodies and can reduce the quality of the waters on the island. As many as 25 students were directly involved in the activity, and 20 residents from the island were directly involved in beach cleaning activities. From this activity, which is centered on the island of South Kabung, 100 kg of garbage has been collected consisting of plastic materials in the form of used drink bottles, stereoforms, pampers, and some trash carried from the middle of the sea, which may be carried away from the mainland coast. This activity is very necessary and is expected to continue as an annual routine activity of the Department of Marine Affairs, as a participation in preserving the sea and maintaining good water quality so that the diversity of species and population of a marine biota is not affected by the presence of these wastes. ===== Pulau Kabung yang berada dalam wilayah Pemerintahan Kabupaten Bengkayang merupakan salah satu dari 226 pulau kecil yang berada di Kalimantan Barat. Kunjungan yang ramai ke pulau tersebut pada musim liburan sekolah dan weekend, menyebabkan banyaknya sebaran sampah yang terdapat di perairan dan pesisir pulau tersebut, dan jika tidak diatasi dengan segera dapat menimbulkan masalah perairan secara global. Tim Dosen Jurusan Kelautan Universitas Tanjungpura sebagai tim pelaksana kegiatan PKM pembersihan pantai pulau Kabung, bersama dengan segenap masyarakat pulau tersebut dan mahasiswa Jurusan Kelautan, terjun membersihkan pantai dan perairan yang dekat dengan permukiman penduduk, memilah dan mengumpulkan sampah, kemudian membakar dan menimbunnya agar tidak semakin menumpuk dan semakin banyak yang masuk dalam badan perairan dan dapat menurunkan kualitas perairan di pulau tesebut. Sebanyak 25 orang mahasiswa terjun langsung dalam kegiatan dan 20 warga masyarakat dari pulau tersebut terlibat langsung dalam kegiatan pembersihan pantai. Dari kegiatan tersebut, yang dipusatkan pulau Kabung Selatan, terkumpul sampah sebesar 100 kg yang terdiri atas bahan plastik berupa botol bekas minuman, styrofoam, popok, dan beberapa sampah bawaan dari tengah laut, yang mungkin terbawa arus dari pesisir daratan. Kegiatan ini sangat perlu dan diharapkan berlanjut sebagai kegiatan rutin tahunan dari Jurusan Kelautan, sebagai peran serta dalam melestarikan laut dan menjaga kualitas perairan tetap baik sehingga keanekaragaman jenis dan populasi suatu biota laut tidak terpengaruh oleh keberadaan sampah-sampah tersebut.